RNA-Seq Reveals the Role of miR-29c in Regulating Inflammation and Oxidative Stress of Bovine Mammary Epithelial Cells - Yang, Jian; Hu, Qi-Chao; Wang, Jin-Peng; Ren, Qian-Qian; Wang, Xing-Ping; Luoreng, Zhuo-Ma; Wei, Da-Wei; Ma, Yun (Frontiers in Veterinary Science, 2022)
Healthy mammary gland is essential for milk performance in dairy cows. MicroRNAs (miRNAs) are the key molecules to regulate the steady state of mammary gland in dairy cows. This study investigated the potential role of miR-29c in bovine mammary epithelial cells (bMECs). RNA sequencing (RNA-seq) was used to measure the transcriptome profile of bovine mammary epithelial cells line (MAC-T) transfected with miR-29c inhibitor or negative control (NC) inhibitor, and then differentially expressed genes (DEGs) were screened. The results showed that a total of 42 up-regulated and 27 down-regulated genes were found in the miR-29c inhibitor group compared with the NC inhibitor group. The functional enrichment of the above DEGs indicates that miR-29c is a potential regulator of oxidative stress and inflammatory response in bMECs through multiple genes, such as forkhead box O1 (FOXO1), tumor necrosis factor-alpha (TNF-α), and major histocompatibility complex, class II, DQ alpha 5 (BoLA-DQA5) in the various biological process and signaling pathways of stress-activated mitogen-activated protein kinase (MAPK) cascade, Epstein-Barr virus infection, inflammatory bowel disease, etc. The results imply that miR-29c plays an important role in a steady state of bMECs or cow mammary gland and may be a potential therapeutic target for mastitis in dairy cows.